Importancia de los servicios complementarios relacionados al bienestar de los estudiantes de la Unidad Educativa “Pujilí” ‘‘cantón Pujilí’’, provincia de Cotopaxi - Bustamante Zambonino, Graciela Maribel (2016)
This research has the general objective: Develop workshops on the importance of ancillary services related to the welfare of students of the Education Unit "Pujilí" Pujilí, Cotopaxi Province. This work is an answer to the problem is: How complementary services affect the welfare of students of the Education Unit "Pujilí" Pujilí the province of Cotopaxi? Where descriptive methodology was used, was developed in the theoretical framework, the fundamental categories with topics and subtopics integration, inclusion and teaching-learning process. Teachers, students and parents surveys were applied to know his thoughts on the benefits provided by the Department of Student Council that generated findings and recommendations. The contribution of the thesis is to develop workshops with students, parents and teachers of the Educational Unit "Pujilí" to allow better development and development and applicability in participants with help from Student Counseling department in this educational establishment.